Identification of Differentiated Learning in Class V of SDN Kabonena - Mutiara, Mutiara; Herlina, Herlina; Asriani, Asriani; Firmansyah, Arif; Sriwahyuni , Sriwahyuni (Journal of Educational Sciences, 2025)
The curriculum is an important guideline in achieving educational goals, which is designed according to the aspirations and needs of students. Government Regulation Number 57 of 2021, concerning National Education Standards emphasizes the importance of curriculum development that is tailored to the characteristics of the region, the character of the educational unit, and the needs of students. This is a form of school independence, where each educational unit is given the widest possible space to develop its own operational curriculum that reflects their own needs and peculiarities.  However, there are still many schools that have not implemented a flexible curriculum optimally. This study aims to describe the implementation of differentiated learning in grade V of SDN Kabonena. Using a qualitative approach of case studies, the results show that teachers have applied the principle of differentiation in aspects of content, process, and learning environment. The materials are tailored to the students' abilities, learning methods vary, and the classroom environment is designed to be comfortable and supports independent learning. However, in the product aspect, there has been no variation in the way students show understanding, due to the limitations of understanding and teachers' ability to implement differentiation. The solution offered is to hold regular training on differentiated learning strategies, as well as facilitate teachers to participate in seminars or learning communities to improve competence in implementing student-centered learning effectively and comprehensively.